Welcome - Editorial Team (The Toro Historical Review, 2022)
Welcome to Volume 13, Issue 1 of The Toro Historical Review! Congratulations to the authors, and a special thank you to our student editorial team who has worked hard and continued to keep us on our regular publication schedule. Thank you! This volume features four essays by history majors Priscilla Avitia, Tatiana Estrada, Johanna Morazan, and Donovan Wright. Originating with research projects in the History 490 capstone course, these essays represent a remarkable achievement in undergraduate research. Well done!